Perancangan Sistem Informasi Pendaftaran Kerja Praktik Berbasis Web Pada Sekretariat DPRD Provinsi Sumatera Utara - Angga Ardiansyah (LKP Unity Academy, 2022)
Practical Work is a student activity to gain knowledge and practical experience in the field based on the scientific basis that has been studied. So far, the process of registering practical work at the DPRD of North Sumatra Province is done manually, to register for practical work students or students must come to the location first. In this way, there are still problems that occur, especially when inputting prospective participant data. The purpose of this research is to design and build a web-based information system that can help participants and also the staff of DPRD North Sumatra Province employees. With this information system, it is hoped that it can help participants and DPRD staff in registering practical work and also in inputting participant data.